Protótipo de asa adaptativa acionada por atuadores de liga com memória de forma - Emiliavaca, Angelo (2020)
The development of the aeronautical industry has led to significant changes in the concepts currently applied to aircraft, whether for civil or military purposes. The impact of these changes on aircraft design and construction is the relentless pursuit of concepts that increase aircraft efficiency over a wider flight spectrum without impacting the safety and reliability of these systems. In this context comes the concept of adaptive aircraft, capable of adapting to the flow by aerodynamic changes without compromising flight safety. One of the concepts used in adaptive aircraft is adaptive wing, with the possibility of varying the curvature of the aerodynamic profile, which is adopted in this work. These structures have some limitations that still need to be developed, such as the actuation system, control system and structural mechanics associated with the shape change. Based on these aspects, this thesis describes the development of a new morphing wing concept, driven by shape memory alloy (SMA) micro spring actuators aiming at an increase in aerodynamic efficiency evaluated from the lift / drag relationship. The developed prototype, called SMArt Morphing Wing, addresses the design of the reconfiguration mechanism, drive system, skin design and wing control system. The deflection limits of the prototype were evaluated showing a controlled deflection of up to 5° on the leading edge and 15° on the trailing edge, reducing drag by 26% compared to a NACA 0012 and increasing the lift / drag ratio by 33% resulting in a better aerodynamic performance from the geometric reconfiguration of the wing.